Application of two Cu(II)-azido based 1D coordination polymers in optoelectronic device: Structural characterization and experimental studies. (9th September 2020) - Mondal, Monotosh; Jana, Sumanta; Drew, Michael G.B.; Ghosh, Ashutosh
Abstract: Two new azido bridged 1D polymeric Cu(II) chains, [Cu(L 1 )( μ 1, 3 -N3 )]∞ (1 ) and [Cu2 (L 2 )2 ( μ 1, 1 -N3 )( μ 1, 3 -N3 )]∞ (2 ) have been synthesized by using two different N2 O donor tridentate reduced Schiff base ligands, HL 1  = 2-[(2-dimethylamino-ethylamino)-methyl]-4-nitrophenol, HL 2  = 2-[(2-diethylamino-ethylamino)-methyl]-4-nitrophenol and both are structurally characterized. Cu(II) ions in both complexes occupy distorted pentacoordinated square pyramidal geometry. Both structures form polymeric chains, in 1, via μ 1, 3 -N3 − while in 2 via both μ 1, 1 -N3 − and μ 1, 3 -N3 − bridges. The band gaps of the complexes (2.91 eV for 1 and 2.89 eV for 2 ) suggest that both polymeric chains are semiconducting and thus possess the potential for uses in devices. A detail I–V analysis was performed to measure device related parameters i.e. effective carrier mobility, transit time, carrier concentration, diffusion length and ideality factor. The results show that both polymeric chains behave as Schottky barrier diodes (SBD) and could be used in opto-electronic device. Between the two complexes, 2 performs better than 1 in terms of applicability as indicated by the calculated parameters. Graphical abstract: One alternating μ 1, 1 and μ 1, 3 -azido and another μ 1, 3 -azido bridged Cu(II) based coordination polymers have been synthesized and characterized. Both of them behave as Schottky Barrier Diode. Image 1 Highlights: Structurally characterized two new Cu(II)-azido bridged 1D polymeric chains. One has μ 1, 3 -N3 − linkage whereas the other is alternating μ 1, 1 -N3 − and μ 1, 3 -N3 − bridged. Both the polymers show well applicability in optoelectronic device fabrication. The one with only μ 1, 3 -N3 − linkage is inferior Schottky Barrier Diode than the other.